SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS PADA BANK PERKREDITAN RAKYAT (BPR) BATANG TARUSAN - Dodi Guswandi (Majalah Ilmiah UPI YPTK, 2018)
The rapidly technology process on globalisasion era in business world, makes the decision making is the important thing to make decision faced with the competition in business world. The decision making can be influence by a few aspect and group, which can influence the decision maker to accelerate the fast, perfectly and correctly the decision making.This software created by using Analytical Hierarchy Process method. Where this algorithm do the process of calculating to get the best decision, using the score group of calculation and compare it with each possibility count of the choosen decision. This software specially will be use to decision support in present credit to PT. BPR Batang Tarusan.From design and the testing the application of decision support system result a correct and flexible decision with all criteria which influence that decision and give a report in order to director can understand why this software choose that decision.